THE INFLUENCE OF ESG PERFORMANCE, LIQUIDITY, CAPITAL STRUCTURE, AND CASH HOLDING ON CORPORATE FINANCIAL PERFORMANCE - Nandita, Olivia Nadya; Luthan, Elvira (Jurnal Akuntansi Bisnis, 2026)
Background: In recent years, the integration of Environmental, Social, and Governance (ESG) considerations has become increasingly important in corporate decision-making, as stakeholders demand greater transparency and accountability regarding corporate sustainability practices. Alongside ESG performance, internal financial factors such as liquidity, capital structure, and retained cash play a crucial role in determining a firm’s ability to maintain operational efficiency and enhance financial performance. However, empirical evidence on how ESG performance and these financial characteristics jointly affect both accounting-based and market-based performance remains inconclusive, particularly in emerging markets such as Indonesia. Objective: This study aims to examine the effect of ESG performance, liquidity, capital structure, and cash holding on the financial performance of non-financial sector companies Research Methods: The research employs a quantitative method using secondary data and a purposive sampling technique, resulting in a sample of 48 companies listed on the Indonesia Stock Exchange (IDX). Hypothesis testing was conducted using multiple linear regression analysis with SPSS 25. Research Results: The results show that ESG performance has a significant positive effect on financial performance (measured by ROA and Tobin’s Q). Liquidity and capital structure have no significant effect on financial performance. Cash holding has a significant positive effect on ROA but does not significantly affect Tobin’s Originality/Novelty of Research: This study examines the impact of ESG performance, liquidity, capital structure, and retained cash on financial performance, measured using two indicators: accounting performance proxied by Return on Assets (ROA) and market performance proxied by Tobin’s Q. The analysis compares non-financial sector companies listed on the Indonesia Stock Exchange (IDX) using data from 2021 to 2023.